2000
DOI: 10.1007/bf02375543
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-ion conducting electrolyte materials for solid oxide fuel cells

Abstract: Abstract. Oxygen-ion conducting solid electrolyte systems have been reviewed with specific emphasis on their use in solid oxide fuel cells. The relationships between phase assemblage, electrolyte stability and ionic conductivity have been discussed. The role of parameters such as sintering temperature and atmosphere which influence the segregation of impurities, present in the starting ceramic powders, at grain boundaries and at the external surface of the electrolyte compacts has been emphasised. The stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
142
1
8

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(165 citation statements)
references
References 92 publications
(87 reference statements)
6
142
1
8
Order By: Relevance
“…Several materials have been proposed as electrolytes in IT-SOFC [13][14][15][16]. Basing on literature data [17,18] as well as own studies [19] tetragonal zirconia: ZrO 2 +3 mol % Y 2 O 3 (3YSZ) can be promising solid electrolyte in IT-SOFC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several materials have been proposed as electrolytes in IT-SOFC [13][14][15][16]. Basing on literature data [17,18] as well as own studies [19] tetragonal zirconia: ZrO 2 +3 mol % Y 2 O 3 (3YSZ) can be promising solid electrolyte in IT-SOFC.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made to reduce the blocking effect in tetragonal zirconia. It was found that the alumina added to the zirconia material acts as the silicon scavenger [14,19,23].…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, poucos óxidos podem satisfazer os rigorosos requisitos deste componente, sendo que os possíveis materiais são a cromita de ítrio (YCrO 3 ) e a cromita de lantânio (LaCrO 3 ) [28]. Tabela III -Materiais empregados na fabricação de eletrólitos usados em SOFCs [23][24][25].…”
Section: Interconectoresunclassified
“…Oxygen-ion conducting ceramic membrane materials (pure ionic or mixed ionic/electronic conductors) have the ability to selectively transport oxygen in the form of an ionic flux at high temperatures producing O 2 of extremely high purity [8,9,43]. Dense membranes constructed from such materials are highly selective to oxygen with a separation factor approaching infinity.…”
Section: Oxygen Separation Membranesmentioning
confidence: 99%